Evaluation of Legal Aid Service Quality and Supervision in Indonesia and Malaysia - Nurani Ajeng Tri Utami; Agus Raharjo; Kuat Puji Prayitno; Setya Wahyudi; Rahadi Wasi Bintoro; Noorfajri Ismail (Lembaga Contrarius Indonesia, 2025)
Indexed Publication (Tier 2)